Nigella sativa and its main constituent, thymoquinone protect against glycerol-induced acute kidney injury in rats - Elham Naderi; Abolfazl Khajavi Rad; Somayeh Nazari; Majid Khazaei; Samira Shahraki; Sara Hosseinian (Mashhad University of Medical Sciences, 2022)
Objective: Rhabdomyolysis is a life-threatening disease caused by releasing myoglobin from injured myocytes, which results in acute kidney injury. In this study, the effect of aqueous-alcoholic extract of Nigella sativa (NS) and thymoquinone (TQ) on rhabdomyolysis-induced kidney damage in rats was investigated.Materials and Methods: There were five groups of rats (n=8): Control, rhabdomyolysis, rhabdomyolysis treated with NS aqueous-alcoholic extract (200 and 400 mg/kg) and TQ (15 mg/kg). Treatments were given for 7 days (two days before and four days after glycerol injection). Glycerol was injected intramuscularly on the third day of the experiment for induction of rhabdomyolysis. Renal function parameters on the first, fourth, and seventh days of the experiment and renal oxidative stress and histological changes at the end of this study were assessed.Results: Glycerol injection caused a significant increase in serum level of urea, creatinine, creatine phosphokinase, urine output and tissue MDA compared to the control animals (p<0.05-0.001). Administration of NS extract and TQ significantly decreased serum urea and creatinine on days 4 and 7, creatine phosphokinase on day 4, and urine output on day 7 compared to the rhabdomyolysis group (p<0.05-0.001). Compared to the rhabdomyolysis group, treatment with NS extract and TQ improved kidney histological abnormalities (p<0.01-0.001). The catalase enzyme activity in the group treated with NS 400 mg/kg and thiol content in the NS 400 mg/kg and TQ groups were significantly higher than those of the rhabdomyolysis group (p<0.05-0.01).Conclusion: NS extract and to some extent TQ protect the kidney from rhabdomyolysis-induced injury.